Exploration of trends in the incidence and prevalence of childhood maltreatment and domestic abuse recording in UK primary care: a retrospective cohort study using ‘the health improvement network’ database - Chandan, Joht Singh (BMJ Open, 2020)
OBJECTIVES: Describe the epidemiology of childhood maltreatment and domestic abuse (in women). DESIGN: Analysis of longitudinal records between 1 January 1995 to 31 December 2018. SETTING: UK primary care database: ‘The Health Improvement Network’ (THIN). PARTICIPANTS: 11 831 850 eligible patients from 787 contributing practices. Childhood maltreatment and domestic abuse (women only) were defined as the presence of a recorded Read code. OUTCOME MEASURES: The incidence rate (IR) and prevalence of childhood maltreatment (in children aged 0–18 years) and domestic abuse (in women aged over 18) between 1996 and 2017. An adjusted incidence rate ratio (aIRR) is given to examine the differences in IRs based on sex, ethnicity and deprivation. RESULTS: The age and gender breakdown of THIN has been previously reported to be representative of the UK population, however, there is substantial missing information on deprivation quintiles (<20%) and ethnicity (approximately 50%). The IR (IR 60.1; 95% CI 54.3 to 66.0 per 100 000 child years) and prevalence (416.1; 95% CI 401.3 to 430.9 per 100 000 child population) of childhood maltreatment rose until 2017. The aIRR was greater in patients from the most deprived backgrounds (aIRR 5.14; 95% CI 4.57 to 5.77 compared with least deprived) and from an ethnic minority community (eg, black aIRR 1.25; 1.04 to 1.49 compared with white). When examining domestic abuse in women, in 2017, the IR was 34.5 (31.4 to 37.7) per 100 000 adult years and prevalence 368.7 (358.7 to 378.7) per 100 000 adult population. Similarly, the IR was highest in the lowest socioeconomic class (aIRR 2.30; 2.71 to 3.30) and in ethnic minorities (South Asian aIRR 2.14; 1.92 to 2.39 and black aIRR 1.64; 1.42 to 1.89). CONCLUSION: Despite recent improvements in recording, there is still a substantial under-recording of maltreatment and abuse within UK primary care records, compared with currently existing sources of childhood maltreatment and domestic abuse data. Approaches must be implemented to improve recording and detection of childhood maltreatment and domestic abuse within medical records.